2020
DOI: 10.1021/jacs.0c06185
|View full text |Cite
|
Sign up to set email alerts
|

Seeded Self-Assembly of Charge-Terminated Poly(3-hexylthiophene) Amphiphiles Based on the Energy Landscape

Abstract: The creation of 1D π-conjugated nanofibers with precise control and optimized optoelectronic properties is of widespread interest for applications as nanowires. “Living” crystallization-driven self-assembly (CDSA) is a seeded growth method of growing importance for the preparation of uniform 1D fiber-like micelles from a range of crystallizable polymeric amphiphiles. However, in the case of polythiophenes, one of the most important classes of conjugated polymer, only limited success has been achieved to date u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 70 publications
2
72
0
Order By: Relevance
“…The NFs have a height of 4.5 nm as determined by atomic force microscopy (fig. S4), a width of 12.8 nm as determined by transmission electron microscopy (TEM), and a solvated corona corresponding to the phosphonium group at the terminus of polythiophene, which permits colloidal stability due to the introduction of electrostatic repulsion between the NFs and additional opportunities for solvation ( 21 ). The predominant NF component is a crystalline core that consists of the rr-P3HT segments ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The NFs have a height of 4.5 nm as determined by atomic force microscopy (fig. S4), a width of 12.8 nm as determined by transmission electron microscopy (TEM), and a solvated corona corresponding to the phosphonium group at the terminus of polythiophene, which permits colloidal stability due to the introduction of electrostatic repulsion between the NFs and additional opportunities for solvation ( 21 ). The predominant NF component is a crystalline core that consists of the rr-P3HT segments ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2.8 μm via living CDSA of a phosphonium-terminated amphiphilic P3HT. 281 Detailed photophysical studies showed that the nanofibers possess estimated diffusions lengths of 300 ± 50 nm, the highest value reported for a conjugated polymer material, and a diffusion constant of 1.1 ± 0.1 cm 2 s −1 . 282…”
Section: Applications Of Particles Accessible Using Living Cdsa Methodsmentioning
confidence: 92%
“…2.8 um via living CDSA of a phosphonium-terminated amphiphilic P3HT. 281 Detailed photophysical studies showed that the nanofibers possess estimated diffusions lengths of 300 ± 50 nm, the highest value reported for a conjugated polymer material, and a diffusion constant of 1.1 ± 0.1 cm 2 s -1 . 282 Coaxial heterojunction nanowires with controlled dimensions have been fabricated through the seeded growth living CDSA with a crystalline energy-accepting outer core-forming poly(3-(2'ethylhexyl)thiophene) (P3EHT) block and a crystalline energy-donating PDHF inner core-forming block.…”
Section: Optoelectronicsmentioning
confidence: 92%
See 1 more Smart Citation
“…[86][87][88][89] Other polymers may be more challenging to adapt to INCP, such as P3HT (which was previously utilized as the soluble block in INCP), despite its ability to form nanofibers and 2Drectangles using other methods. 61,62,[90][91][92][93][94][95] Similarly, poly(3octylthiophene) (which forms nanowires) 96 and poly [3-(2,5,8,11-tetraoxatridecanyl)thiophene] (which forms nanoribbons) 97 would also be challenging due to their side chains which provide good solubility.…”
Section: Perspectivementioning
confidence: 99%